Entity Framework 4.1: expert's cookbook : more than 40 recipes for successfully mixing test driven development, architecture, and Entity Framework code first /: more than 40 recipes for successfully mixing test driven development, architecture, and Entity Framework code first. (©2012) - Unknown
No abstract available